Expressão das caderinas nos tumores mamários em cadelas - Piekarz, C. H.; Biondo, A. W.; Amorim, Renée Laufer [UNESP]; Rodaski, S.; Barros Filho, Ivan Roque; De Nardi, A. B. (My University, 2008)
Mammary tumors are among the most common neoplasia of canine females. The occurrence of metastasis may be detected by proteic markers. Among them, exist the E-cadherin, a member of cadherin family known for its important role in the regulation of intercellular adhesion in epithelial tissues. Studies suggest that E-cadherin may function as a tumor and invasion suppressor molecule. Cadherin activity is regulated by multiple mechanisms, including interaction with other proteins such as catenins. In this review, the authors approach the cadherin family and other related adhesion proteins including its function, physiopathology and potential use as marker for diagnosis and prognosis of canine mammary tumors.
Cadherin expression in canine mammary tumors
Keywords: Cadherin; Dog; Immunohistochemistry; Mammary neoplasi; Canis familiaris